Analysis of Domestic Wastewater Management Systems in Low Income Residential Areas - Dody Eko Prasetyo; Heni Fitriani; Betty Susanti (Sriwijaya Journal of Environment, 2020)
Statistically, access to proper sanitation in Muara Enim Regency reaches 90.75% in 2018, but it needs to be ascertained whether it is safe in the context of no latrine leak that can pollute the environment, especially in areas with the lowest level of population welfare. Muara Lawai village is the village that has the highest number of poor and near poor people and villages with status as underdevelop village in Muara Enim District. Based on an analysis of existing conditions, the facilities for wastewater sanitation infrastructure used by low-income communities (MBR) and non-MBR in Muara Lawai Village were found to be still not feasible and safe. Efforts to provide adequate and safe sanitation infrastructure that can be implemented in Muara Lawai Village are a off-site domestic settlement wastewater system with initial service coverage for 41 households or 205 people. total wastewater generation (Qr) 16.40 m3 / day with peak discharge (Qpeak) of 54.82 m3 / day, minimum discharge (Q min) 2.33 m3 / day and infiltration discharge (Qinf) 12.96 m3 / day, so the design discharge is obtained at 67.78 m3 / day. Calculation results in the service sub-system required a special PVC waste pipe with a roughness value (manning) of 0.012 with details of house connections pipe size 4"along 212.1 m, service pipe size 6" along 178.8 m and main pipe size 8"along 220.7 m. The need for control tubs is 31 units installed at each pipe meeting with a size of 50 x 50 x 50 cm. In the processing sub-system (WWTP building), the processing technology used is anaerobic biofilter with the overall dimensions of the WWTP building of 7.5 x 2.0 x 2.5 m.